2007
DOI: 10.1038/ni1525
|View full text |Cite
|
Sign up to set email alerts
|

'Role reversal' for the receptor PAR1 in sepsis-induced vascular damage

Abstract: Sepsis is a deadly disease characterized by considerable derangement of the proinflammatory, anti-inflammatory and coagulation responses. Protease-activated receptor 1 (PAR1), an important regulator of endothelial barrier function and blood coagulation, has been proposed to be involved in the lethal sequelae of sepsis, but it is unknown whether activation of PAR1 is beneficial or harmful. Using a cell-penetrating peptide (pepducin) approach, we provide evidence that PAR1 switched from being a vascular-disrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
265
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 218 publications
(285 citation statements)
references
References 56 publications
15
265
2
3
Order By: Relevance
“…Multiple studies have been performed to determine the specificity of pepducins to their cognate receptors. 22,[31][32][33][34] We found that PAR1 pepducins based on the i1 and i3 loops had comparable efficacy in inhibiting migration and Ca 2ϩ signaling. In contrast, i3-targeted pepducins also could block PAR1-dependent ERK1/2 activity and VEGF secretion.…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…Multiple studies have been performed to determine the specificity of pepducins to their cognate receptors. 22,[31][32][33][34] We found that PAR1 pepducins based on the i1 and i3 loops had comparable efficacy in inhibiting migration and Ca 2ϩ signaling. In contrast, i3-targeted pepducins also could block PAR1-dependent ERK1/2 activity and VEGF secretion.…”
mentioning
confidence: 72%
“…Pepducins are lipidated peptides that are specifically targeted to the intracellular surface of their cognate GPCR, resulting in modulation of signal transduction. 21,22,31,32,50,51 Pepducins targeting the PAR1 i3 loop completely inhibited cell motility, calcium mobilization, and ERK1/2 activation. In contrast, the i1-targeted PAR1 pepducin inhibited cell motility, but did not have any effect on ERK1/2 activation and only partially suppressed calcium mobilization.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations